Choice of location for bacterial blight evaluation in common bean - Silva, L.O. da; Pastor Corrales, Marcial A.; Singh, S.P. (1990)
Comparative results are given on the evaluation of bacterial blight in bean germplasm carried out in the glasshouse and in the field. (CIAT)